tRNA-derived small RNAs: their role in the mechanisms, biomarkers, and therapeutic strategies of colorectal cancer - Bo Zhang; Yanru Pan; Zhe Li; Kefeng Hu (Journal of Translational Medicine)
Abstract Colorectal cancer (CRC) is the third most prevalent malignancy and the second leading cause of cancer-related mortality worldwide, with an increasing shift towards younger age of onset. In recent years, there has been increasing recognition of the significance of tRNA-derived small RNAs (tsRNAs), encompassing tRNA-derived fragments (tRFs) and tRNA halves (tiRNAs). Their involvement in regulating translation, gene expression, reverse transcription, and epigenetics has gradually come to light. Emerging research has revealed dysregulation of tsRNAs in CRC, implicating their role in CRC initiation and progression, and highlighting their potential in early diagnosis, prognosis, and therapeutic strategies. Although the clinical application of tsRNAs is still in its early stages, recent findings highlight a close relationship between the biogenesis and function of tsRNAs, tRNA chemical modifications, and the tumor immune microenvironment (TIME). Additionally, similar to other small RNAs, tsRNAs can be effectively delivered via nanoparticles (NPs). Consequently, future research should focus on elucidating the clinical significance of tsRNAs concerning base modifications, TIME regulation, cancer immunotherapy, and NPs delivery systems to facilitate their clinical translation.